2020
DOI: 10.1371/journal.pone.0236337
|View full text |Cite
|
Sign up to set email alerts
|

Students under lockdown: Comparisons of students’ social networks and mental health before and during the COVID-19 crisis in Switzerland

Abstract: This study investigates students' social networks and mental health before and at the time of the COVID-19 pandemic in April 2020, using longitudinal data collected since 2018. We analyze change on multiple dimensions of social networks (interaction, friendship, social support, co-studying) and mental health indicators (depression, anxiety, stress, loneliness) within two cohorts of Swiss undergraduate students experiencing the crisis (N = 212), and make additional comparisons to an earlier cohort which did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

95
1,027
8
44

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,139 publications
(1,325 citation statements)
references
References 45 publications
95
1,027
8
44
Order By: Relevance
“…While the population had not been required to be in quarantine, it was strongly recommended for people to remain at home during the time of the data collection. As in Israel, first studies conducted in Switzerland among student populations suggest that COVID-19 specific worries, lack of interaction and emotional support, and physical isolation were associated with negative mental health trajectories [e.g., (40)]. Unemployment rates in Switzerland were reported to be 3.3% in April and 3.4% in May.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…While the population had not been required to be in quarantine, it was strongly recommended for people to remain at home during the time of the data collection. As in Israel, first studies conducted in Switzerland among student populations suggest that COVID-19 specific worries, lack of interaction and emotional support, and physical isolation were associated with negative mental health trajectories [e.g., (40)]. Unemployment rates in Switzerland were reported to be 3.3% in April and 3.4% in May.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…[7,12,15,[21][22][23][24][25][26][27] and social life (closed dorms and therefore moving back home, no meetings with friends, university colleagues, relatives, no parties, no traveling, staying trapped overseas etc.) [7,13,[29][30][31], as well as their financial situation (losing a student's job, worries about own financial situation, about future education and career) [14,32,33] and emotional health (fears, frustrations, anxiety, anger, boredom etc.) [7,14,28,29,34].…”
Section: Introductionmentioning
confidence: 99%
“…Besides many challenges, the COVID-19 pandemic brought also some positive changes in habits and mindsets, such as paying more attention to personal hygiene, taking care of their own (quitting smoking, eating organic food from local farms) and relatives' health, especially of those in risk groups, taking more time for doing sports, etc. [30,33,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-national study with university students found associations between loneliness and subjective health status, such as sleeping problems, tobacco use, aggressive behavior, injury, and sexual risk behavior (Peltzer and Pengpid 2017). Furthermore, students have become even more affected by loneliness due to the absence of face-toface contact caused by the social isolation measures adopted to reduce the COVID-19 spread (Elmer et al 2020).…”
Section: Objectivesmentioning
confidence: 99%